(untitled) (SAARC Journal of Agriculture, 2014)
The study was conducted to develop a cytology based diagnostic tool for the diagnosis of avian Mycoplasma and E. coli infections at post mortem in the field condition. A total of 38 culture and PCR confirmed Mycoplasma, E. coli or mixed infected samples were used for this study. Lung impression smears were prepared on glass slide from the samples at post mortem examination. Inflammatory cells were counted on microscope after Giemsa staining. Cell counts were analyzed with Bonferroni joint confidence interval and Mann-Whitney U test. The average cell percentages in healthy cases were 73.54- 81.66%, 9.63-13.37% and 7.42-14.38% for lymphocyte, heterophil, and macrophage, respectively. In case of Mycoplasma infection, average percentages of lymphocyte, heterophil and macrophages were 82.01-88.10%, 5.6 to 8.16% and 4.52 9.68%, respectively. In E. coli infection, average percentage of lymphocyte, heterophil and macrophages were found as 64.44-70.76%, 19.73-23.47% and 8.9- 12.7%, respectively. In mixed infection, lymphocyte, heterophil and macrophage were found as 76.08-80.50%, 13.47 17.63% and 4.56 7.66%, respectively. Statistical analyses revealed that in Mycoplasma infection number of lymphocyte and in E. coli infection number of heterophil increased significantly (p< 0.01). In MC complex, number of heterophil increased and macrophages decreased significantly (p < 0.01). These findings could help identification of Mycoplasma, E. coli or Mycoplasma- E. coli complex at post mortem examination in the field condition. DOI: http://dx.doi.org/10.3329/sja.v10i2.18331 SAARC J. Agri., 10(2): 95-105 (2012)